Dying at Grace - Thompson, Bill ca. 20. Jh (<<The>> Criterion collection, 2010)
"Director Allan King documents the final months of five terminally ill cancer patients at the Toronto Grace Health Centre." [filmdienst.de]
Original: Kanada 2003
Bildformat 1.77:1 (16:9)
Keywords: Toronto Grace Health Centre; Sterbender; Krebskranker; Palliativmedizin; Film; DVD-Video